The Impact of Burnout on Police Officers’ Performance and Turnover Intention: The Moderating Role of Compassion Satisfaction - Gabriela Pedro Gomes; Neuza Ribeiro; Daniel Roque Gomes (Administrative Sciences, 2022)
Burnout should be seen as an important phenomenon influencing the services provided by police forces, due to its high exposure to stressful events. The study sought to examine the impact of burnout on performance and turnover intention of Portuguese police forces, as well as to analyze the moderating effect of compassion satisfaction (CS) on this relationship. Data were collected in 2021 from 1.682 Portuguese police officers, using individual surveys. The results showed that (1) burnout is negatively related to performance; (2) burnout is positively related to turnover intention; (3) CS, although it has a positive effect on performance, does not assume a moderating role, as expected, in the relationship between burnout and performance; (4) CS assumes a moderating role in the relationship between burnout and turnover intention. That is, when a person who still suffers from burnout feels CS, it decreases the intention to leave the organization. The implications and the bearings of this study are discussed and presented regarding the theoretical, empirical and practical perspectives in order to better support both the comprehension of burnout in police officers and offer the best practical recommendations.